Aplikasi Kompos Kulit Buah Kakao Terhadap Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pembibitan Utama - Rizeki Eka Wani; Sampoerno '; Edison Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The process of developing oil palm cultivation is closely associated with the availaibility of quality seed. Quality seed is very determining the growth and production of such commodities. Supply of cocoa peel’s compost into the soil may increase the availability of nutrient elements both macro and micro. The research is aimed to know the influence of of cocoa peel’s compost on the growth of the oil palm seeds in the main nursery. The research was carried out experimentally by using Completely Randomized Design (CRD) with consists of four treatments and three replication. The results of research that application of cocoa peel’s compost to the oil palm seed is significantly to seed height increment, but not significantly to the number of leaves, diameter of excrescence, the ratio of the editorial root and dry weight. The application of cocoa peel’s compost with increasingly high doses tend to increase diameter of excrescence and dry weight of oil palm seed, while on parameters the number of leaves and the ratio of the editorial root not tend to increase of growing oil palm seed. The application 150 g compost/polybag or same with 37,5 ton/ha, shows the best growth of oil palm seed. Key Word : Cocoa Peel’s Compost, Oil Palm Seed